Method of generating and navigating a 3-D representation of a hierarchical data structure - Karen Theisen; Eugene Jhong (2001)
A method of generating a graphical representation of a hierarchical data structure to on a display unit, the hierarchical data structure including a first node having at least one content item. A graphic tree representative of the hierarchical data structure is displayed on the display unit, the graphic tree including a first graphic representation of the first node. A second graphic representation, associated with the first graphic representation, that provides a representation of a content item (e.g., a file) is displayed on the display unit, the second graphic representation differing in appearance from the first graphic representation.